U-Statistics : Theory and Practice - Lee, A. J. (Boca Raton: CRC Press, 1990)
In 1946 Paul Halmos studied unbiased estimators of minimum variance, and planted the seed from which the subject matter of the present monograph sprang. The author has undertaken to provide experts and advanced students with a review of the present status of the evolved theory of U-statistics.
Keywords: Mathematical statistics